Qualitative Test of Protein in Tempeh Wrapped in Leaf and Plastic - Panjaitan, Riong Seulina; Purwati, Purwati; Elawati, Nur; Ghassani, Fatiha Azka; Suryo, Nabila Dwi; Salsabilla, Zuli Astuti; Simatupang, Angel Maria; Afikah, Hana Tri; Langit, Vinsensia Asahi Sulan (Indonesian Journal of Pharmaceutical Research, 2024)
Tempeh is a food familiar to Indonesians made from fermented soybeans wrapped in leaves or plastic. Protein identification in tempeh is carried out to detect the presence of protein using a qualitative test based on the color changes that form. The aim of this research is to provide scientific information about the qualitative comparison of protein content in samples of tempeh wrapped in leaves and tempeh wrapped in plastic. The qualitative protein identification methods used in this research are the biuret test, the ninhydrin test, the xantoprotein test, the sulfur test, and the Neuman test. From the observations, it can be seen that the biuret test, ninhydrin test, xanthoprotein test, and sulfur test gave positive results for both types of tempeh samples. Meanwhile, in the Neumann test, tempeh with plastic wrapping gave negative results compared to tempeh wrapped in leaves, which gave positive results.